Relationship between microscopic analysis and quantitative and qualitative indicators of moisture susceptibility evaluation of warm-mix asphalt mixtures containing modifiers - Pooyan Farazmand; Parham Hayati; Hamid Shaker; Sajad Rezaei (Fracture and Structural Integrity)
Given the defects of bitumen in asphalt mixtures particularly exposed to moisture, this study mainly aims to investigate the relationship between qualitative and quantitative results of moisture susceptibility tests on asphalt mixtures modified by ZycoTherm, nanoclay, nanosilica and SBS. The Marshall stability, modulus of resilience and indirect tensile strength tests are carried out. Boiling water and SEM qualitative tests are also used. Eventually, the qualitative tests results are digitalized through image processing by MATLAB and compared with the moisture susceptibility results of indirect tensile strength test.